Executive functions and memory strategies in healthy individuals with high and low cognitive reserve: A comparative study - Cunha, Maria João (2023)
Objective: In this study, we aim to explore differences in executive functions, mem- ory, and memory strategies, between healthy individuals with high and low levels of Cognitive Reserve (CR). Method: A total of 70 participants underwent neuropsychological assessment, 36 females and 34 males, aged between 50 and 85 years. The instruments administered were BSI, MoCA, QRC, LMS I and II (EMW-III), DMS (WAIS – III), TMS, VFT, SCWT, and WCST. Results: We confirm the influence of the CR, including education level, on the per- formance of the neuropsychological tests, with higher CR and education level lead- ing to better neuropsychological performance. At the TMS test, there were no group differences in those conditions with higher demand on executive functions, while in those with the material externally organized the differences were significant. While age had a lesser influence on performance, middle-aged participants with a higher CR presented better performances, when compared to older participants.Conclusions: Results suggest that the use of memory strategies is more effective in participants whose executive functioning is preserved, regardless of age. A greater capacity for coding structured word patterns, was observed, compared to unstruc- tured patterns. It was also found that a higher level of cognitive reserve enhanced the participants cognitive performance.